Effectiveness of perampanel as the only add‐on: Retrospective, multicenter, observational real‐life study on epilepsy patients. Issue 4 (22nd September 2022) - Gasparini, Sara; Ferlazzo, Edoardo; Neri, Sabrina; Cianci, Vittoria; Iudice, Alfonso; Bisulli, Francesca; Bonanni, Paolo; Caggia, Emanuele; D'Aniello, Alfredo; Di Bonaventura, Carlo; DiFrancesco, Jacopo C.; Domina, Elisabetta; et al.
Abstract: Objective: Perampanel (PER) is indicated as adjunctive antiseizure medication (ASM) in adolescents and adults with epilepsy. Data from clinical trials show good efficacy and tolerability, while limited information is available on the routine clinical use of PER, especially when used as only add‐on treatment. Methods: We performed an observational, retrospective, multicenter study on people with focal or generalized epilepsy aged >12 years, consecutively recruited from 52 Italian epilepsy centers. All patients received PER as the only add‐on treatment to a background ASM according to standard clinical practice. Retention rate, seizure frequency, and adverse events were recorded at 3, 6, and 12 months after PER introduction. Subanalyses by early or late use of PER and by concomitant ASM were also conducted. Results: Five hundred and three patients were included (age 36.5 ± 19.9 years). Eighty‐one percent had focal epilepsy. Overall, the retention rate was very high in the whole group (89% at 12 months) according with efficacy measures. No major differences were observed in the subanalyses, although patients who used PER as early add‐on, as compared with late add‐on, more often reached early seizure freedom at 3‐month follow‐up (66% vs 53%, P  = .05). Treatment‐emergent adverse events occurred in 25%, far less commonly than in PER randomized trials. Significance: This study confirms the good efficacy and safety of PER for focal or generalized epilepsy in real‐life conditions. We provide robust data about its effectiveness as only add‐on treatment even in patients with a long‐standing history of epilepsy and previously treated with many ASMs.